Analysis of long‐term survival after hepatectomy for isolated liver metastasis of gastrointestinal stromal tumour. Issue 11 (19th June 2013) - Cheung, Tan To; Chok, Kenneth S. H.; Chan, Albert C. Y.; Yau, Thomas C. C.; Chan, See Ching; Poon, Ronnie T. P.; Fan, Sheung Tat; Lo, Chung Mau
Abstract Background In the treatment of liver metastasis of gastrointestinal stromal tumour (GIST), the role of hepatectomy is controversial. This study tried to identify such role by investigating the immediate and long‐term surgical outcomes. Methods Data of patients who underwent hepatectomy to treat their metastatic disease were reviewed. Patients whose liver tumours were confirmed to be metastatic GISTs were included for analysis. Clinicopathological characteristics of the primary disease, time of metastasis development and modes of treatment were recorded. Immediate outcome and long‐term survival after hepatectomy were analysed. Results Ten patients were confirmed to have isolated liver metastasis of GIST. Their median age was 61 (42–74) years. All of them had normal liver function and no cirrhosis. Seven patients received major hepatectomy and three patients received minor hepatectomy. The median operation time was 319.5 (122–735) min. The median tumor size was 5.5 (1.5–15) cm. No hospital death occurred. The 1‐, 3‐ and 5‐year overall survival rates were 100, 75 and 50%, respectively and the corresponding disease‐free survival rates were 70, 42 and 14%, respectively. Conclusion Treating isolated liver metastasis of GIST with hepatectomy is effective and safe. Favourable long‐term overall survival and disease‐free survival can be achieved.